PSYCHOLOGICAL PROBLEMS AFFECTING YOUTH'S PROFESSIONAL CHOICE - Turakulov B.N.; Abduqodirova D.E. (Bright Mind Publishing, 2025)
This article discusses in detail the social problems that arise among young people in today's developing era in choosing the right profession and choosing a profession, as well as the psychological processes and problems that affect them.
Keywords: Profession, problem, choice of profession, youth, professional skills, school, family, psychologist, psychological problems.